A point mutation in the zinc-finger transcription factor CqLOL1 controls the green flesh color in chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How) - Peng, Jiazhu; Gao, Yin; Qiao, Yanchun; Wang, Guoping (Frontiers in Plant Science, 2024)
Flesh color is an essential trait in chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How), however, the inheritance and molecular basis of green flesh trait remain unclear. Methods: In the present study, two F2 populations, derived from 1742 (white flesh) × FJ3211 (green flesh) and J16 (white flesh) × FJ5 (green flesh), were used to identify the green flesh (Cqgf) locus.Results: Genetic analysis revealed that the presence of green flesh was a quantitative trait that closely followed a normal distribution. Combining the results from QTL mapping and BSA-seq analysis, the Cqgf locus was preliminarily determined to be located on chromosome 05 and was narrowed down to a 2.55 Mb interval by linkage analysis. A large J16 × FJ5 F2 population comprising 3180 individuals was subsequently used to screen the recombinants, and the Cqgf locus was fine mapped to a region of 329.70 kb that harbors six genes. One of the candidate genes, Bch05G003700, the zinc-finger transcription factor LOL1 (lsd one like 1 protein; CqLOL1), was the strongest candidate gene for the Cqgf locus according to sequence variation and expression analysis. Additionally, a point mutation (A > C) in CqLOL1 resulted in the substitution of threonine (T) with proline (P) in the amino acid sequence, showing a complete relationship linked with flesh color in a panel of 45 germplasms.